Different Gene Preferences of Maple Syrup Urine Disease in the Aboriginal Tribes of Taiwan - Jia-Woei Hou; Tsann-Long Hwang (Elsevier, 2014)
Maple syrup urine disease (MSUD) is a rare inborn error of metabolism caused by a deficiency of the branched-chain α-ketoacid dehydrogenase (BCKD) complex. Mutations in any one of the three different genes encoding for the BCKD components, namely, BCKDHA, BCKDHB, and DBT, may be responsible for this disease. In Taiwan, few MSUD cases were diagnosed clinically, and most of these patients are from Aboriginal tribes. Materials and methods: To identify and detect the carrier frequency of MSUD in Taiwanese Aboriginal tribes, we performed biochemical and molecular studies from peripheral blood in MSUD patients and dried blood on filter paper in the enrolled screened populations. Results: Homozygous A208T and I281T of BCKDHA were found in two patients from Hans (non-Aboriginal Taiwanese), respectively; compound heterozygous mutations of the DBT gene [4.7 kb deletion/c.650-651insT (L217F or L217fsX223) and c.650-651insT/c.88-89delAT] were found in two patients from Amis, respectively, after direct DNA sequencing and polymerase chain reaction-restriction fragment length polymorphism studies. There were no cases of deleted 4.7-kb heterozygote out of 302 normal people (Hans, n = 125; Atayal, n = 156; and Saisiyat, n = 21); by contrast, the DBT mutations c.650-651insT and deleted 4.7-kb heterozygote were noted in 2/121 and 1/121, respectively, from the general population of the Amis, a southeastern Taiwanese tribe. Conclusion: Although the Taiwanese Austronesian Aboriginal tribes are considered to share a common origin, different gene preferences of MSUD were noted. The novel DBT mutation c.650-651insT was more prevalent than the deleted 4.7-kb heterozygote in the Amis population. The reported 4.7-kb deletion indicating a possible founder mutation may be preserved in the southern and eastern, but not in northern Aboriginal tribes of Taiwan.